Giant intrathyroidal parathyroid adenoma - Ramon Vilallonga; Carlos Zafón; Raul Migone; Juan Antonio Baena (Journal of Emergencies, Trauma and Shock, 2012)
Primary hyperparathyroidism (PHPT) is not an uncommon endocrine disorder. However, acute primary hyperparathyroidism, or parathyroid crisis (PC), is a rare clinical entity characterized by life-threatening hypercalcemia of a sudden onset in patients with PHPT. We describe a patient with PC who presented with acute worsening of depressive symptoms, nausea and vomiting, and required emergency surgery. Serum calcium, alkaline phosphatase, and parathyroid hormone were elevated and serum phosphorus was low. An emergency hemithyroidectomy was performed because of none medical control of hypercalcemia. A giant intrathyroidal parathyroid adenoma was diagnosed. PHTP can be a life-threatening situation for patients, requiring immediate surgical treatment. A giant intrathyroidal parathyroid adenoma is an uncommon cause of PC.